ASPECTS OF THE INFLUENCE OF PRICES ON CONSUMER BEHAVIOUR WHEN PURCHASING FOODSTUFFS: ANALYSIS OF CASES FROM SOFIA, BULGARIA - Borislav ATANASOV (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Foodstuffs have a strong presence in the daily lives of households. As a rule, consumers make purchases taking into account the prices of goods and the income they can spend on a purchase. Food prices are not constant, but a dynamic quantity. Based on the data of the National Statistical Institute of Bulgaria, it has been established that household expenditure for foodstuffs amounts to about 30% of total consumer expenditure. The main objective of this study is to track the dynamics of price changes overall as well as by groups of foodstuffs in Bulgaria, the dynamics of the changes of the total consumer income and of the consumer expenditure for the purchase of foodstuffs, and their influence on end consumers’ behaviour. Based on the data available at the National Statistical Institute of Bulgaria, the article presents the consumer price index, the indices of the total consumer income and of the total consumer expenditure of households for the period 2015-2021. A comparison has been made between the general price index and the index of the prices of foodstuffs and soft drinks. An analysis of the indices of the prices of individual groups of foodstuffs has been carried out. On the basis of quantitative research carried out by the author by using an online survey, aspects of consumer attitudes are revealed that are based on price influence upon purchase. One-dimensional frequency distributions were used for this purpose.